Investigating the Optical Phase Conjugation Reconstruction Phenomenon of Light Multiply Scattered by a Random Medium - Snow H. Tseng (IEEE Photonics Journal, 2010)
The optical phase conjugation (OPC) phenomenon of light multiply scattered through a macroscopic scattering medium is simulated using the pseudospectral time-domain (PSTD) technique. We investigate the OPC reconstruction from scattered light at various positions in space. Specific results show that the original incident light cannot be reconstructed from singly scattered light. To reconstruct the original incident light, an “unbiased” selection of scattered light is required.